2019
DOI: 10.1007/s12307-019-00226-0
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate Kinase M2: a Metabolic Bug in Re-Wiring the Tumor Microenvironment

Abstract: Metabolic reprogramming is a newly emerged hallmark of cancer attaining a recent consideration as an essential factor for the progression and endurance of cancer cells. A prime event of this altered metabolism is increased glucose uptake and discharge of lactate into the cells surrounding constructing a favorable tumor niche. Several oncogenic factors help in promoting this consequence including, pyruvate kinase M2 (PKM2) a rate-limiting enzyme of glycolysis in tumor metabolism via exhibiting its low pyruvate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 181 publications
0
12
0
Order By: Relevance
“…Zheng et al reported that PKM2 could promote the translocation of NF-κB/P65 to the nucleus and thus induce cancer cell migration and invasion in ovarian cancer 15 . PKM2 is also overexpressed in other cells in the TME and affects the activation of T and B cells, the immune response of macrophages and dendritic cells, and the recruitment of myeloid-derived suppressor cells in tumors 12 . CAFs are a highly heterogeneous population, which is derived from different cell types 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zheng et al reported that PKM2 could promote the translocation of NF-κB/P65 to the nucleus and thus induce cancer cell migration and invasion in ovarian cancer 15 . PKM2 is also overexpressed in other cells in the TME and affects the activation of T and B cells, the immune response of macrophages and dendritic cells, and the recruitment of myeloid-derived suppressor cells in tumors 12 . CAFs are a highly heterogeneous population, which is derived from different cell types 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In the nucleus, PKM2 functions as a protein kinase and a transcriptional co-activator of many genes associated with cancer cell proliferation, metastasis, and apoptosis 11 . For example, it can promote cancer cell metastasis by upregulating matrix metalloproteinase-2 (MMP2), MMP9, N-cadherin, and vimentin and can promote tumor cell growth by upregulating β-catenin expression 12 , 13 . PKM2 is also involved in the regulation of the NF-κB signaling pathway in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…In tumor cells and inflammatory cells, there is the transformation from a PKM2 tetramer to a PKM2 monomer/dimer (27,28). TEPP-46 and DASA-58 are two different small-molecule agonists of PKM2 and both can promote the formation of the PKM2 tetramer, which can not only inhibit the growth of tumor cells but also inhibit the inflammatory response of immune cells by promoting the formation of the PKM2 tetramer (29)(30)(31). In the latest research, Le et al found that PKM2 activator TEPP-46 attenuates b-aminopropionitrile fumarate (BAPN)-induced mouse model of thoracic aortic aneurysm and dissection (TAAD) by inhibiting NLRP3 inflammasome-mediated IL-1b secretion.…”
Section: Discussionmentioning
confidence: 99%
“…The PKM2 tetramer is located in the cytoplasm and is the active form of the enzyme; the PKM2 dimer and monomer are located in the nucleus and play an important role in regulating gene transcription (27,28). Growing evidence suggests that the transition from a PKM2 tetramer to a PKM2 monomer/dimer (nuclear translocation) plays an important role in promoting the inflammatory response and tumor invasion and proliferation (29)(30)(31). LPS induces the formation of the PKM2 monomer/dimer, promotes the transcription of high mobility group box 1 (HMGB1) and NF-kB through interaction with hypoxia-inducible factor 1a (HIF-1a), and further promotes the release of the inflammatory factor IL-1b, which plays an important role in the development of sepsis (32).…”
Section: Introductionmentioning
confidence: 99%
“…(1) Although, tumors are heterogenic and possess different characteristics, some basic characteristics remain the same which are called "hallmarks of cancer". (2) These hallmarks include six main characteristics composed of hyper-proliferation, evading growth suppressors, angiogenesis, invasion and metastasis, resistance to cell death, and replicative immortality. In addition to these six capabilities, two emerging hallmarks have been added resistance to immune destruction and cell metabolism reprogramming.…”
mentioning
confidence: 99%